Diversity of wet and mesic grasslands along a climatic gradient on the southern margin of the Pannonian Basin. Issue 4 (9th August 2020) - Škvorc, Željko; Ćuk, Mirjana; Zelnik, Igor; Franjić, Jozo; Igić, Ružica; Ilić, Miloš; Krstonošić, Daniel; Vukov, Dragana; Čarni, Andraž
Abstract: Questions: Which are the main wet and mesic grassland vegetation types along the climatic gradient on the southern margin of the Pannonian basin? Which are the most important environmental gradients that determine their distribution and species composition? Location: The southern margin of the Pannonian plain (N and E Slovenia, N Croatia, N Serbia). Methods: A database of 2, 575 vegetation plots originally assigned to the Molinio ‐ Arrhenatheretea was compiled. Semi‐supervised classification based on the K ‐means algorithm was applied to assign plots into 12 a‐priori alliances and to search for new alliances. Non‐metric Multidimensional Scaling (NMDS) ordination with Ellenberg's indicator values and bioclimatic variables were applied to show the influence of ecological conditions on species composition. The plots within each alliance were further classified into associations using the beta flexible method. Results: Classification resulted in 12 alliances recognized in the EuroVegChecklist, and two new groups appeared. The first group occurs in the eastern part of the research area, where many ruderal species appear. This group was treated as a new alliance, Salvio nemorosae ‐ Arrhenatherion forming a vicariant syntaxon of the alliance Arrhenatherion . The second group occurs in the western part. It is a transitional group between mesic ( Arrhenatherion ) and wet meadows ( Deschampsion ) and can be treated as Alopecurion . Besides, three new associations and six new subassociations were described, together with the typification of seven associations and of three subassociations. Numerical analyses revealed floristic, ecological and geographical differentiation among analysed vegetation types. Conclusions: The communities showed typical Central European features in the western part, but their floristic and ecological conditions changed towards the eastern part, where the continental influence was more pronounced. The vegetation structure and plant species composition in the studied area were influenced by soil moisture and soil nutrient availability as well as by strong biogeographical and climatic gradients. Abstract : Our research deals with floristic and ecological differentiation of mesic to humid semi‐natural meadows and pastures along a macroclimatic gradient at the southern edge of the Pannonian plain. In this gradient, various vegetation types appear reflecting also microclimatic conditions and management practices. We evaluated their floristic composition, ecology and distribution, as well as their correspondence with Annex I of EU Habitat Directive 92/43/EEC.